FAKTOR-FAKTOR YANG MEMPENGARUHI IBU DALAM PEMBERIAN ASI EKSKLUSIF KEPADA BAYI DI PUSKESMAS SEBANGKAU KECAMATAN PEMANGKAT KABUPATEN SAMBAS - Fricilia, Rodhiya; Agustiansyah, Agustiansyah (Pontianak Nutrition Journal, 2018)
Exclusive breastfeeding is only breastfeeding without additional food and drinks in infants aged 0-6 months. Even water is not given in this exclusive breastfeeding stage. Breast milk is a fat emulsion in a solution of protein, lactose, and organic salt secreted by the two halves of the mother’s breast gland, as the main food for the baby. The composition of breast milk is not the same from time to time, this is based on lactation stage (Setiowati, 2010). This study aims to determine the relationship between knowledge, attitudes, maternal work and promotional media for formula milk with exclusive breastfeeding at the Puskesmas in the District of Pemangkat, Sambas Regency. The type of research used is the survey method with a cross sectional study approach. Sampling was done by purposive sampling with a sample of 57 mothers. Data analysis was performed using the chi-square test. The results showed that there was no relationship between the knowledge of mothers with exclusive breastfeeding (p = 0.054), there was no relationship between the attitudes of mothers with exclusive breastfeeding (p = 0.933), there was no correlation between the work of mothers with exclusive breastfeeding (p = 0.962) , and there is no relationship between the promotion media of formula milk with exclusive breastfeeding (p = 0.985). It was concluded that of all the variables tested there was no relationship with exclusive breastfeeding in infants in the Puskesmas that was as far as Pemangkat District, Sambas Regency. It is recommended that mothers give exclusive breastfeeding to their babies until they are 6 months old.